An Exploration of Arabic Vocabulary in Gorontalo Communication Community: A Contrastive Perspective in Arabic Language Learning - Hairuddin, Hairuddin; Sarif, Suharia; Kadir, Suleman D.; Amin, Saifuddin (Institut Agama Islam Negeri (IAIN) Kendari, 2024)
This study aimed to explore the influence of Arabic vocabulary absorption in the communication of the Gorontalo community and its impact on Arabic language learning. The research’s background was the long-term interaction between the Gorontalo and Arabic languages through Islamic religious teaching, which led to significant changes in the phonology, morphology, and semantics of the Gorontalo language. This research employed a qualitative method with a descriptive and contrastive analysis approach. Data were collected through observation, interviews, and documentation in Limboto District, focusing on Pone and Biyonga villages. The study identified over 150 Gorontalo vocabulary words absorbed from Arabic, spanning various aspects of daily life, both religious and secular. Phonological and morphological changes demonstrated adaptation processes, while semantic changes reflected contextualization within the local culture. These findings underscored the importance of contrastive-based Arabic teaching approaches tailored for Gorontalo speakers, aiming to enhance the effectiveness of language learning. By addressing the specific linguistic characteristics of the Gorontalo language, such strategies could improve learners’ understanding and retention of Arabic vocabulary. In conclusion, this study provides significant insights into the linguistic interplay between Arabic and Gorontalo, offering a foundation for developing more contextualized and effective language learning strategies. It contributes to the broader field of sociolinguistics and language pedagogy.